The gut–microbiota–brain changes across the liver disease spectrum - Higarza, Sara G.; Arboleya, Silvia; Arias, Jorge L.; Gueimonde, Miguel; Arias, Natalia (Frontiers in Cellular Neuroscience, 2022)
Gut microbiota dysbiosis plays a significant role in the progression of liver disease, and no effective drugs are available for the full spectrum. In this study, we aimed to explore the dynamic changes of gut microbiota along the liver disease spectrum, together with the changes in cognition and brain metabolism. Sprague-Dawley rats were divided into four groups reflecting different stages of liver disease: control diet (NC); high-fat, high-cholesterol diet (HFHC), emulating nonalcoholic steatohepatitis; control diet + thioacetamide (NC+TAA), simulating acute liver failure and high-fat, high-cholesterol diet + thioacetamide + (HFHC+TAA) to assess the effect of the superimposed damages. The diet was administered for 14 weeks and the thioacetamide was administrated (100 mg/kg day) intraperitoneally over three days. Our results showed changes in plasma biochemistry and liver damage across the spectrum. Differences at gut microbiota compositional level were found among the experimental groups. Members of Enterobacteriaceae family were most abundant on HFHC and HFHC+TAA groups and Akkermansiaceae on NC+TAA group, albeit being lactobacilli genus dominant in NC group. Moreover, liver harm affected diversity and bacterial community structure, with a lost in rare species. Indeed, the superimposed damage group (HFHC+TAA) suffered a lost on both rare and abundant species. Behavioral evaluation has shown that HFHC, NC+TAA and HFHC+TAA displayed a worsened execution when discriminating the new object. Also, NC+TAA and HFHC+TAA were not capable of recognizing the changes in place of the object. Furthermore, working memory was affected in HFHC and HFHC+TAA groups, whereas NC+TAA group displayed a significant delay in the acquisition. Brain oxidative metabolism changes were observed in the prefrontal, retrosplenial and perirhinal cortices, as well as the amygdala and mammillary bodies. Besides, groups administered with thioacetamide presented an increased oxidative metabolic activity in the adrenal glands. These results highlight the importance to cross-compare along the liver spectrum to understand the different gut-microbiota-brain changes. Furthermore, our data point out specific gut microbiota targets in order to design more effective treatments thought the liver-gut-brain axis focused on specific stages of liver disease.